الكلام الانشائي الطلبي في قصيدة البردة الحسنية الحسينية فى مدح أل خير البرية لسيد صالح الجعفري - nur nafiudin (Pascasarjana UIN Raden Mas Said Surakarta, 2024)
In the science of rhetoric, constructive speech is speech that does not intend to be truthful or untruthful. It is divided into two parts: on-demand and non-demand. This research investigates the science of meanings, especially in requesting constructional speech. From the above-mentioned data, this research was searching for the poetic compositional speech in the poem Al-Burda Al-Hassaniyyah Al-Husseini in praise of Al-Khair Al-Bariyyah by Sayyid Saleh Al-Jaafari. The type of this research is qualitative research using a library study. The basic data used in this research is the book “The Poem of Burdah Al-Hassaniyyah Al-Hussainiya in Praise of the Good of Al-Bariyyah” by Sayyid Saleh Al-Jaafari. The source of data in this research is from books on rhetoric. The results of this research are as follows: It contains 73 forms of the requesting constructional speech, meaning 29 of the imperative form, with three meanings: guidance, threat, and supplication. Then 12 of the form of prohibition with four meanings: guidance, contempt, threat, and supplication. Then 13 of the interrogative form with four meanings: guidance, information, multiplication, and magnification. Then 5 of the form of wishing with two prohibitions: the hope that cannot be achieved and the hope that may be possible. Then 14 of the form of the call with three meanings: originality, glorification, and supplication.